Associations between cortical thickness and reasoning differ by socioeconomic status in development. (April 2019) - Leonard, Julia A.; Romeo, Rachel R.; Park, Anne T.; Takada, Megumi E.; Robinson, Sydney T.; Grotzinger, Hannah; Last, Briana S.; Finn, Amy S.; Gabrieli, John D.E.; Mackey, Allyson P.
Highlights: Thickness of RLPFC positively relates to reasoning in 4–7-year olds from lower, but not higher, SES backgrounds. The positive relationship between RLPFC thickness and reasoning was also present in a sample of 12–16-year olds from lower-SES backgrounds. Young children with strong reasoning from lower-SES backgrounds uniquely showed positive relationships between RLPFC thickness and age. This work suggests that the neural structure that supports reasoning varies by SES during development. Abstract: Although lower socioeconomic status (SES) is generally negatively associated with performance on cognitive assessments, some children from lower-SES backgrounds perform as well as their peers from higher-SES backgrounds. Yet little research has examined whether the neural correlates of individual differences in cognition vary by SES. The current study explored whether relationships between cortical structure and fluid reasoning differ by SES in development. Fluid reasoning, a non-verbal component of IQ, is supported by a distributed frontoparietal network, with evidence for a specific role of rostrolateral prefrontal cortex (RLPFC). In a sample of 115 4–7-year old children, bilateral thickness of RLPFC differentially related to reasoning by SES: thicker bilateral RLPFC positively correlated with reasoning ability in children from lower-SES backgrounds, but not in children from higher-SES backgrounds. Similar results were found in an independent sample of 59 12–16-year old adolescents. Furthermore, young children from lower-SES backgrounds with strong reasoning skills were the only group to show a positive relationship between RLPFC thickness and age. In sum, we found that relationships between cortical thickness and cognition differ by SES during development.